2015
DOI: 10.1002/ijc.29395
|View full text |Cite
|
Sign up to set email alerts
|

High IDH1 expression is associated with a poor prognosis in cytogenetically normal acute myeloid leukemia

Abstract: The prognostic value of IDH1 mutations has been systematically evaluated in acute myeloid leukemia (AML) patients recently. However, the role of IDH1 expression in AML is still under exploration. To investigate the clinical significance, we analyzed the IDH1/2 expression in 320 patients with cytogenetically normal AML (CN-AML) by quantitative real-time reverse-transcription polymerase chain reaction. High expression of IDH1 was predominant in patients with FLT3-ITD and DNMT3A mutations and less prevalent in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 27 publications
(60 reference statements)
4
30
1
Order By: Relevance
“…TET2 was decreased in cervical squamous cell carcinoma along with %5-hmC, and low levels in patients were shown to be associated with a poor prognosis [52]. In contrast to our results, another team observed that high expression of IDH1 is associated with shorter overall survival in cytogenetically normal acute myeloid leukemia [53]. In epithelial ovarian cancer, TET2 and %5-hmC decreased compared with normal controls, and this low expression was associated with poor overall survival of the patients [54].…”
Section: Discussioncontrasting
confidence: 94%
“…TET2 was decreased in cervical squamous cell carcinoma along with %5-hmC, and low levels in patients were shown to be associated with a poor prognosis [52]. In contrast to our results, another team observed that high expression of IDH1 is associated with shorter overall survival in cytogenetically normal acute myeloid leukemia [53]. In epithelial ovarian cancer, TET2 and %5-hmC decreased compared with normal controls, and this low expression was associated with poor overall survival of the patients [54].…”
Section: Discussioncontrasting
confidence: 94%
“…Favorable subgroups included t(8;21)/ AML1-ETO and inv16/ CBFβ-MYH11 ; adverse consisted of t(9;22), inv(3)/t(3;3), -5, -7, del(5q), del(7p), 11q23 and complex translocations; intermediate subtype contained cytogenetically normal and AML with other cytogenetic abnormalities. Patients received HAA (homoharringtonin 2 mg/m 2 /day for 7 days, cytarabine 100 mg/m 2 /day for7 days and aclarubicin 20 mg/m 2 /day for 5 days), DA (daunorubicin 45 mg/m 2 /day for 3 days and cytarabine 100 mg/m 2 /day for 7 days) and IA regimen (idarubicin 8–10 mg/m 2 /day for 3 days and cytarabine 150 mg/m 2 /day for 7 days) [2, 19]. In the consolidation therapy, younger patients were treated with a high-dose cytarabine-based chemotherapy [19].…”
Section: Methodsmentioning
confidence: 99%
“…Patients received HAA (homoharringtonin 2 mg/m 2 /day for 7 days, cytarabine 100 mg/m 2 /day for7 days and aclarubicin 20 mg/m 2 /day for 5 days), DA (daunorubicin 45 mg/m 2 /day for 3 days and cytarabine 100 mg/m 2 /day for 7 days) and IA regimen (idarubicin 8–10 mg/m 2 /day for 3 days and cytarabine 150 mg/m 2 /day for 7 days) [2, 19]. In the consolidation therapy, younger patients were treated with a high-dose cytarabine-based chemotherapy [19]. The chemotherapy consolidation for elderly patients was decided by the physicians in an individualized manner, as described previously [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CN -AML was defined as AML with the karyotype 46, XY [20] or 46 XX [20] in all 20 metaphase cells analyzed. Patients were treated with intensive induction chemotherapy as previous reported2324. In the consolidation therapy, younger patients were treated with a high-dose cytarabine-based chemotherapy23.…”
Section: Methodsmentioning
confidence: 99%